2013
DOI: 10.1111/pme.12083
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality System Combined with Biofeedback for Treating Pediatric Chronic Headache—A Pilot Study

Abstract: This novel system, combining biofeedback and virtual reality, is feasible for pediatric use. Randomized controlled studies in larger populations are needed in order to determine the utility of the system in reducing headache, improving daily functioning, and elevating quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 37 publications
(38 reference statements)
1
56
0
2
Order By: Relevance
“…Request permissions from permissions@acm.org. VR has also proven to be an effective method to reduce perceived pain during burn wound care [12]. Hoffman et al designed a series of distraction-based VR studies in which patients reported up to 50% reduction in perceived pain.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Request permissions from permissions@acm.org. VR has also proven to be an effective method to reduce perceived pain during burn wound care [12]. Hoffman et al designed a series of distraction-based VR studies in which patients reported up to 50% reduction in perceived pain.…”
Section: Related Workmentioning
confidence: 97%
“…In 2013, Shiri et al created a VE and biofeedback system to treat pediatric headaches [12]. They obtained galvanic skin response (GSR) levels of patients with chronic headaches over ten sessions, each lasting 30 minutes.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, totally immersive VR was shown to have greater benefit in pain reduction . ‐ As immersive VR technology improves, VR is being utilized as a complementary therapy for persistent, chronic pain rather than solely for acute pain . On the basis of these data and our recognition that novel complementary therapies are required to improve pain management in patients with SCD, we aimed to conduct a feasibility study of immersive VR therapy in patients hospitalized for vaso‐occlusive pain.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports along these lines have already been published, one example being experiments involving VR hypnosis. 23,24 In the introduction to this paper, we mentioned other examples 10,11 in which VR has been used for purposes other than pain distraction, and these could be particularly useful in the clinical context. What makes the intervention described here especially interesting and innovative is that it is designed to change cognitive variables (i.e., self-efficacy and catastrophizing) that have been shown to be very important in the context of chronic pain problems.…”
Section: Discussionmentioning
confidence: 99%